Optimation of Buffer Solution and K2C2O4 Reductor to Fe(II)-1,10-fenantrolin Determination using Spectrophotometric UV-Vis - Dhita Ariyanti; Djarot Sugiarso (Akta Kimia Indonesia, 2018)
Iron was needed in the world to all components, so it was important to determine iron’s concentrate. This research determined buffer pH optimation and the consentration of K2C2O4 reductor. Reduction of 5 ppm Fe3+ to Fe2+ have been investigated. The first experiment was determination of λmaks and  than various pH and concentration of K2C2O4 as reductor in order that determination of optimum condition. The result showed that λmaks was 520 nm and pH 4,5 with 3 ppm of K2C2O4 was effective to reduce 5 ppm of Fe3+ to Fe2+ in acid conditions forming [(Fe(C12H8N2)3]2+ complex by spectrophotometric UV-Visible. But in base solution, this complex was not formed. Both acid and base conditions were effective and accurate, case of value of RSD under 20 ppt and CV under 2%. This indicator showed  that this method was good.